Induction of Apple Cucumber (Cucumis melo) Buds Development by Combination of Kinetin and IAA In B5 (Gamborg) Medium - Pritha Nour Mustikawaty; Nurcahyo Widyodaru Saputro (Universitas Wiralodra, 2021)
Research on indirect organogenesis of apple cucumber (Cucumis sp.) Was conducted from June until August 2020. The aim of the study is to get the best results from IAA and Kinetin concentrations on the growth of buds organogenesis to apple cucumber plants (Cucumis sp.) in B5 Gamborg Medium. The method used was an experimental method with nonparametric statistics with 25 treatments that were repeated 5 times and analyzed descriptively by the Kruskal Wallis test. The results showed that growth of apple cucumber shoots at the best combination treatment of IAA and Kinetin that is at concentrations 2,5x10-7 IAA and 3,2x10-5 Kinetin (A3B1) which resulted in appear shoots time at 39 days after initiation (hsi), it can provide the best growth of shoot height of 0,4 cm and the highest number of a shoot is 3. However, treatment with concentration 2,0x10-7 M IAA and 4,4x 10-5 Kinetin (A2B2) resulted in appearing shoots time at 39 days after initiation (hsi) and shoot height of 0,35 cm.